Is the atherosclerotic phenotype of pre-eclamptic placentas due to altered lipoprotein concentrations and placental lipoprotein receptors?: role of a small-for-gestational-age phenotype - Hentchke, Marta; Poli-de-Figueiredo, Carlos; Pinheiro da Costa, Bartira; Kurlak, L.O.; Williams, Paula Juliet; Mistry, Hiten D. (American Society for Biochemistry and Molecular Biology, 2013)
Artherosis of spiral arteries in uteroplacental beds from pre-eclamptic women resemble those of atherosclerosis, characterised by increased plasma lipids and lipoproteins. We hypothesised 1) lipoproteins receptors/transporter in placenta would be up-regulated in pre-eclampsia, associated with increased maternal and fetal lipoprotein concentrations; 2) expression of these would be reduced in pre-eclamptic placentae from women delivering small-for-gestational-age (SGA) infants. Placental biopsies, maternal and umbilical serum samples were taken from 27 normotensive and 24 pre-eclamptic women. Maternal/umbilical cord serum LDL; HDL; total cholesterol and triglycerides were measured. Placental mRNA expression of lipoprotein receptors/transporters were quantified using qRT-PCR. Protein localisation/expression of LRP-1 in the pre-eclamptic with/without SGA was measured by immunohistochemistry. Placental mRNA expression of all genes except PON-1, MTTP and PDIA2 were observed. No differences for any lipoprotein receptors/transporters were found between groups; however, in the pre-eclamptic group placental LRP-1 expression was lower in SGA delivering mothers (n = 7; P=0.036). LRP-1 protein was localised around fetal vessels and Hofbauer cells. This is the first detailed study of maternal/fetal lipoprotein concentrations and placental lipoprotein receptor mRNA expression in normotensive and pre-eclamptic pregnancies. These findings do not support a role of altered lipid metabolism in pre-eclampsia, but may be involved in fetal growth.